'Break the rules or quit the job': physical education teachers' experiences of physical contact in their teaching practice. Issue 4 (4th May 2023) - Varea, Valeria; Öhman, Marie
ABSTRACT : Physical contact between teachers and students in physical education (PE) has been a troubling, complex and unsolved issue. Research has shown that PE teachers struggle with high levels of fear, insecurity and anxiety when it comes to physical contact with students. However, most of the research conducted so far has focused on a few countries and in regard to the dominant no-touch societal discourse related to sexual connotations. Research from other countries on PE-related touch and other non-sexual physical contact topics is still missing from the literature. This paper aims to explore touch within the PE arena in Argentina and France. Data were generated with a group of eight PE teachers, four from France and four from Argentina. Results suggest that even though teachers were well aware of the widely spread discourse regarding sexual harassment, they discussed the concerns of touch in PE in different ways. Touch was considered necessary for both emotional support and the avoidance and treatment of injuries. In some cases, teachers were concerned about the admissibility of touch involving students with religious beliefs, and some acts of violence. The conclusions of this study reveal a shift in the 'risks' surrounding teacher-student physical contact, and the less-discussed presence of risks other than those related to sexual implications when considering other countries. The conclusions also revolved around the changes of PE teachers' professional subjectivities over the last few decades.